Hubungan Status Gizi Dan Praktik 3M Dengan Kejadian DBD Di Kota Bengkulu Tahun 2022 - Putri Ramayani; Ida Samidah; Fiya Diniarti; Jipri Suyanto (Gayaku Publisher, 2022)
Dengue Hemorrhagic Fever (DHF) or Dengue Haemorrhagic Fever (DHF), commonly called Dengue Haemorrhagic Fever (DHF), is a disease caused by the dengue virus, which is transmitted by Aedes Aegypti and Aedes Albopictus mosquitoes. The World Health Organization (WHO) states that the number of reported cases of dengue fever has increased more than eightfold over the last four years, from 505,000 cases in 2013 to 4.2 million in 2019. Based on data from the Ministry of Health for 2020, cases of dengue hemorrhagic fever (DHF) in Indonesia reached 71,700 cases. According to data from the Bengkulu Provincial Health Office, the incidence of DHF in Bengkulu Province is relatively high, with morbidity and mortality rates above the national target. There were 1,261 cases of DHF that occurred in Bengkulu Province in 2020 (Bengkulu Provincial Health Office, 2020). This research is a quantitative descriptive analytic research with a case-control design, namely an analytic observation research conducted by comparing the case group and the control group based on their exposure status (retrospective). This design moves from the effect (illness) to the cause (exposure). aims to determine whether there is a relationship between nutritional status and 3M practises and the incidence of DHF. The results of this study show that there is a relationship between nutritional status and the incidence of DHF in Bengkulu City in 2022, and there is a relationship between 3M practises and the incidence of DHF in Bengkulu City in 2022.